• Предмет: Алгебра
  • Автор: sahzodasaukatovna
  • Вопрос задан 6 лет назад

Решите неравенство: . (9-х)(6х+1)(х-7) ≥ 0

Ответы

Ответ дал: sergejmaksim65
0

Ответ:

1) х+2,6=3,4

х=3,4-2,6

х=0,8

2) 6х=1,2

х=1,2:6

х=0,2

3) 3х-8=15

3х=15+8=23

х= 23:3

х=7,6

4) 2х-3=5х-27

2х-5х=-27+3

-3х=-24

х=24:3

х=8

5)5 (х-2)+3х=6

5х-10+3х=6

5х+3х=6+10

8х=16

х=16:8

х=2

6) 6х-2 (4х-1)=7

6х-8х+2=7

6х-8х=7-2

-2х=5

-х=5:2

-х=2,5

х=-2,5

7) 0,2х-0,1(2х-6)=0,6

0,2х-0,2х+0,6=0,6

0,2х-0,2х=0,6-0,6

0=0

8) х-5 (х+4)=2 (х-8)+8

х-5х-20=2х-16+8

х-5х-2х=20-16+8

-6х=12

-х=12:6

-х=2

х=-2

9)х+22+8 (х-2)=3 (4-х)

х+22+8х-16=12-3х

х+8х+3х=-22+16+12

12х=6

х=6:12

х=0,5

10)х-4,2=6,9

х=6,9+4,2=11,1

х=11,1

11)0,3х=15

х=15:0,3=50

х=50

12) 3х-24=6х+3

3х-6х=3+24

-3х=27

-х=27:3

-х=9

х=-9

13) 5 (х-8)-4 (5х+2)=12

5х-40-20х-8=12

5х-20х=12+40+8

-15х=60

-х=60:15

-х=4

х=-4

14) 2х-4 (х-3)=5 (х+1)-9

2х-4х+12=5х+5

2х-4х-5х=-12+5

-7х=-7

х=7:7

х=1

все что смог

Объяснение:

Ответ дал: esenalinurmaral
0

(9-х) (6х+1) (х-7)≥ 0

9-х=0 6х+1=0 х-7=0

-х=-9 6х=-1 Х=7

х=9 х=-1/6

ответ:(-∞;-1/6]∪ [7;9]

Приложения:
Похожие вопросы